Mito, história e individuação do feminino no candomblé: as imagens arquetípicas da guerreira, da amante e da mãe - Souza, Larissa Fernandes Caldas (2015)
This dissertation aims to address the women in Candomblé according to a rescue archetypal and mythic as the framework for the study and analysis of individuation in the yard of women. Taking as a methodology fieldwork, nine women were interviewed whose "orixá head" three female deities: Iansã, Oxum and Yemanja. In semi-structured interviews, we seek to address three key aspects: the myths of deities, the history of women in Candomblé and the journey of the women interviewed in the process before, during and after the making. It analyzes the importance of mythical narratives, the archetypal traits and how the process of individuation is presented in the trajectory of speeches from the moment of making up their own daily experiences of the interviewees. As a theoretical framework, we seek to Jung and Eliade to dialogue with the composition of the rites in Candomblé, the plot of myths and influence of archetypal images of deities studied as warriors, lovers and mothers. This study investigates the hypothesis of a mythical and archetypal influence of deities in the process of individuation of the interviewees after making process in Candomblé as relevance highlight these female deities present in Candomblé as archetypal and integrating figures that inspire and reflect the roots of our Brazilian society. This study is important to highlight these female deities present in Candomblé as archetypal and integrating figures that inspire and reflect the roots of our own Brazilian society. Because in their religion these women find their "inner goddess" in her head Orisha.